A new nonparametric test of cointegration rank - George Kapetanios (Queen Mary University of London, Department of Economics, 2003)
This paper suggests a new nonparametric testing procedure for determining the rank of nonstationary multivariate cointegrated systems. The asymptotic properties of the procedure are determined and a Monte Carlo study is carried out.
Keywords: C32; C14; 330; Cointegration rank; Nonparametric analysis; Kointegration; Nichtparametrisches Verfahren; Ranking-Verfahren